2010
DOI: 10.1016/j.applthermaleng.2010.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Study of turbulent heat transfer of aviation kerosene flows in a curved pipe at supercritical pressure

Abstract: a b s t r a c tThe flow and heat transfer characteristics of China No. 3 aviation kerosene in a heated curved tube under supercritical pressure are numerically investigated by a finite volume method. A two-layer turbulence model, consisting of the RNG kee two-equation model and the Wolfstein one-equation model, is used for the simulation of turbulence. A 10-species kerosene surrogate model and the NIST Supertrapp software are applied to obtain the thermophysical and transport properties of the kerosene at vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…Their experimental results were compared with the conventional formulas of DittuseBoelter [11] and SiedereTate [12]. Zhong et al [13] inspected the fluid flow and heat transfer of China RP-3 aviation kerosene at supercritical pressure; and showed that the heat transfer was strengthened greatly when the inner wall temperature was over 600 K. Li et al [14] numerically studied the flow and heat transfer of China RP-3 aviation kerosene at supercritical pressure under the effect of body force. All the above-mentioned researches showed that the complicated thermophysical properties of aviation kerosene at supercritical pressure caused a non-common convective heat transfer, and the heat transfer enhancement occurred when the wall temperature was near the pseudo-critical temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Their experimental results were compared with the conventional formulas of DittuseBoelter [11] and SiedereTate [12]. Zhong et al [13] inspected the fluid flow and heat transfer of China RP-3 aviation kerosene at supercritical pressure; and showed that the heat transfer was strengthened greatly when the inner wall temperature was over 600 K. Li et al [14] numerically studied the flow and heat transfer of China RP-3 aviation kerosene at supercritical pressure under the effect of body force. All the above-mentioned researches showed that the complicated thermophysical properties of aviation kerosene at supercritical pressure caused a non-common convective heat transfer, and the heat transfer enhancement occurred when the wall temperature was near the pseudo-critical temperature.…”
Section: Introductionmentioning
confidence: 99%
“…As for numerical studies, Li et al [9] investigated heat transfer of RP3 kerosene under supercritical pressures and found that enhancement does not always happen when the inner wall temperature is higher than the critical temperature of kerosene. Effects of centrifugal force on heat transfer were also studied [10]. The numerical research of Hua et al [11] for n-heptane indicates that heat transfer deterioration happens when inner wall temperature is higher than the pseudocritical temperature.…”
Section: Introductionmentioning
confidence: 99%
“…However, the work conditions, such as the heat flux, the mass flow rate, and the size of the cooling channels, are different from those in a practical scramjet [12]. [8] 0 ∼55 8498∼51000 1.7, length 100 Hydrofining kerosene Li et al [9,10] 0.3, 0.4, 0.5, 0.6 530∼1061 12, length 4500 RP3 Hua et al [11] 1, 3, 5, 7 5857∼15597 2, length 300 n-Heptane Wang et al [15] 1, 3, 5, 7 4180∼12542 2, length 300 Methane Ruan and Meng [16] 3 , 5 , 7 6 2 7 1 2 × 1, 2 × 2, 2 × 3 M e t h a n e Table 1 has summarized the work conditions in the previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…In the same time, for its special properties such as high density, low viscosity and low sound speed, supercritical fluid is widely used in industries, such as active cooling in scramjet, 1,2 high pressure steam turbine, organic Rankine cycle etc. due to its moderate critical pressure and temperature, and low sound speed as Figure 1 shows.…”
Section: Introductionmentioning
confidence: 99%